Developmental and Cognitive Characteristics of "High-Level Potentialities" (Highly Gifted) Children - Laurence Vaivre-Douret (Hindawi Limited, 2011)
This study covers the interesting field of the development in gifted children which is often neglected in pediatrics because psychomotor development data are still rare, since "gifted" children are generally noticed towards the end of their primary schooling by IQ measurement. Developmental studies have shown the evidence from several fields that children identified as "high-level potentialities" or "intellectually gifted" develop sensory, locomotor, neuropsychological, and language skills earlier than typically expected. The hypothesis is offered that the earlier development originates from biological processes affecting the physical development of the brain and in turn even intellectual abilities are developed earlier, potentially allowing for advanced development. Further it is discussed how these developmental advances interact with the social environment and in certain circumstances may entail increased risk for developing socioemotional difficulties and learning disabilities that often go unaddressed due to the masking by the advance intellectual abilities.